Supervision Criminal Policy In Indonesian Criminal Law Reform - Rahmanul Mursyid; Ani Purwanti (Jurnal Ilmu Sosial Mamangan, 2022)
The supervision of criminal policy requires a comprehensive study. In the 2019 Criminal Code Bill, supervision crimes are included in the main crime category. In order to realize just punishment, it must be seen from various perspectives, including the procedures for implementing supervision of criminal supervision. The method used is normative juridical research, namely research to examine the application of positive law principles or norms and an inventory of positive law, to find legal principles and doctrines. With the first approach to legislation (statute approach), it is possible to comprehend the hierarchy and principles of statutory provisions. The second approach is the Conceptual Approach, which examines concepts, theories, and expert opinions associated with the object of research, as well as the viewpoints or doctrines that evolve in the science of law. The results of the study show that the repressive paradigm of retributive justice has changed to a paradigm of restorative justice-based punishment. This can be seen in the formulation of the New Criminal Code Bill, one of which is supervision punishment as a new crime, supervision punishment is an alternative to conditional deprivation of liberty. However, supervision punishment in the Criminal Code Bill is still common, so a policy is needed to formulate the Ius Constituendum concept of supervision punishment, such as supervision procedures that must be conceptualized early on, hence the implementation of supervision punishment can run effectively.Â Â